Noninvasive Chromosome Screening for Evaluating the Clinical Outcomes of Patients With Recurrent Pregnancy Loss or Repeated Implantation Failure - Xi, Haitao; Qiu, Lin; Yao, Yaxin; Luo, Lanzi; Sui, Liucai; Fu, Yanghua; Weng, Qiuyi; Wang, Jing; Zhao, Junzhao; Zhao, Yingzheng (Frontiers in Endocrinology, 2022)
This retrospective cohort study explores whether noninvasive chromosome screening (NICS) for aneuploidy can improve the clinical outcomes of patients with recurrent pregnancy loss (RPL) or repeated implantation failure (RIF) in assisted reproductive technology. A total of 273 women with a history of RPL or RIF between 2018 and 2021 were included in this study. We collected data of all oocyte retrieval cycles and single blastocyst resuscitation transfer cycles. For the patients experiencing RPL, NICS reduced the miscarriages rate per frozen embryo transfer (FET), improved the ongoing pregnancies rate and live birth rate: 17.9% vs 42.6%, adjusted OR 0.39, 95% CI 0.16–0.95; 40.7% vs 25.0%, adjusted OR 2.00, 95% CI 1.04–3.82; 38.9% vs 20.6%, adjusted OR 2.53, 95% CI 1.28–5.02, respectively. For the patients experiencing RIF, the pregnancy rates per FET in the NICS group were significantly higher than those in the non-NICS group (46.9% vs. 28.7%, adjusted OR 2.82, 95% CI 1.20–6.66). This study demonstrated that the selection of euploid embryos through NICS can reduce the miscarriage rate of patients experiencing RPL and improve the clinical pregnancy rate of patients experiencing RIF. Our data suggested NICS could be considered as a possibly useful screening test in clinical practice.